2008
DOI: 10.1038/hdy.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

Association genetics in Pinus taeda L. II. Carbon isotope discrimination

Abstract: Dissection of complex traits that influence fitness is not only a central topic in evolutionary research but can also assist breeding practices for economically important plant species, such as loblolly pine (Pinus taeda L). In this study, 46 single nucleotide polymorphisms (SNPs) from 41 disease and abiotic stress-inducible genes were tested for their genetic association with carbon isotope discrimination (CID), a timeintegrated trait measure of stomatal conductance. A familybased approach to detect genotype/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
79
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(87 citation statements)
references
References 69 publications
8
79
0
Order By: Relevance
“…The SNP‐by‐SNP association approach has shown that the effect of each SNP on the total phenotypic variation is generally low, which is expected for multigenic control and may also suggest complex gene interaction effects (González‐Martínez et al ., 2008; Prunier et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The SNP‐by‐SNP association approach has shown that the effect of each SNP on the total phenotypic variation is generally low, which is expected for multigenic control and may also suggest complex gene interaction effects (González‐Martínez et al ., 2008; Prunier et al ., 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Association studies involving candidate genes have been successful to detect genetic polymorphisms associated with phenotypic variation in loblolly pine (González-Martínez et al, 2008), Douglas fir (Eckert et al, 2009b), Sitka spruce (Holliday et al, 2010) and white spruce .…”
Section: Introductionmentioning
confidence: 99%
“…This trend indicates that larger sets of genes should be analyzed in conifers to get a more complete picture of LD of the gene space. The information obtained should contribute to build more efficient gene SNP arrays for use in association studies (González-Martínez et al, 2008) and for outlier detection among natural populations or environments (Namroud et al, 2008;Prunier et al, 2011). Accordingly, we sequenced a large number of genes in natural populations of white spruce to assess LD and its contributing factors more completely, and to compare with results obtained for other conifers.…”
Section: Introductionmentioning
confidence: 99%
“…In P. pinaster it was validated that δ 13 C may be used as a surrogate for WUE (Fernandez et al, 2006), is linked to other hydraulic traits in Pinaceae (Martinez-Villalta et al, 2004) and might have higher heritability than other measures of WUE (McKay et al, 2003). On the other hand, the trait shows a remarkable environmental influence, and consequently needs to be tested in a wide range of environments with a rigorous environmental control, and the complexity of the trait, which involve several functional candidate gene types, might complicate validation of genotype/phenotype associations for WUE (Gonzalez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%